Principles of Genetics - Gardner, Eldon John Simmons, Michael J (John Wiley & Sons, 1991)
An examination of the field of genetics, with an emphasis on applications. Written primarily for students, this book provides up-to-date coverage of the most recent techniques used in modern genetics, such as gene cloning and plot analyses of genes and gene products.